3D CT volumetric analysis of spinal canal volume in Bichon Frisé, Dachshund, and French Bulldog: correlation with neurologic severity in thoracolumbar disc herniation - Voiculeț, Ionuț Claudiu; Purdoiu, Robert Cristian; Lăcătuș, Radu; Lucaci, Felix Daniel; Patrichi, Teodora Sonia; Farkas, István; Beteg, Florin Ioan; Tudor, George; Mârza, Sorin Marian (Frontiers in Veterinary Science, 2026)
IntroductionThe intervertebral disc herniation (IVDH) is one of the most common causes of spinal injury in dogs. Certain breeds, notably chondrodystrophic dogs, are predisposed to severe thoracolumbar IVDH due to anatomical and genetic factors.MethodsThis study applied three dimensional (3D) volumetric imaging analysis to compare the spinal canal volume and to investigate the relationship between canal volume and neurological symptoms severity. We retrospectively analyzed 21 dogs (7 Bichon Frisé, 7 Dachshund and 7 French Bulldogs) with imaging confirmed thoracolumbar disc herniation. Computed tomography (CT) scans were segmented using 3D Slicer to quantify the bony spinal canal volume from the cranial to caudal end of the vertebral column.Results and discussionsFrench Bulldogs showed a significantly larger mean spinal canal volume than those of Dachshunds and Bichons (p < 0.05 for both comparisons). Across all dogs, smaller canal volumes were associated with more severe neurological deficits (Spearman ρ ≈ −0.72, p = 0.0014). Across all breeds, disc herniations were most frequently observed at the thoracolumbar junction (T12–L2; 5 of 21 cases), but substantial overlap existed with neighboring segments. The thoracolumbar junction is especially susceptible to disc herniation because it is a transition zone between the rigid thoracic spine and the mobile lumbar spine, where mechanical stress is concentrated and spinal canal reserve space is limited. The 3D volumetric analysis of the vertebral canal is a feasible adjunct to routine imaging and reveals significant breed specific differences. Narrower canal volume appears to exacerbate the impact of disc herniation on the spinal cord, suggesting that canal size is a contributing risk factor for neurologic severity. A critical volume threshold (~1,700 mm3 per vertebral segment) was observed, under which dogs were markedly more likely to develop severe deficits.